2017
DOI: 10.1136/bjophthalmol-2017-311345
|View full text |Cite
|
Sign up to set email alerts
|

Vision in former very low birthweight young adults with and without retinopathy of prematurity compared with term born controls: the NZ 1986 VLBW follow-up study

Abstract: ACTRN12612000995875, Pre-results .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 29 publications
4
46
4
2
Order By: Relevance
“…Approximately 2% of preterm birth survivors are diagnosed with blindness, and visual acuity is impaired compared to those born at term [279][280][281][282]. Moreover, among adolescents who were born preterm, 50% have vision-related problems [283].…”
Section: Eyesmentioning
confidence: 99%
“…Approximately 2% of preterm birth survivors are diagnosed with blindness, and visual acuity is impaired compared to those born at term [279][280][281][282]. Moreover, among adolescents who were born preterm, 50% have vision-related problems [283].…”
Section: Eyesmentioning
confidence: 99%
“…12 Retinopathy of prematurity (ROP) is one of the complications of preterm birth. It can have a negative impact on the future visual function 8,13 of preterm individuals and is related to other impairments, although this association could be mediated by other neonatal risk factors. 8 Between 1988 and 1990, a prospective population-based study was conducted on the incidence of ROP in preterm infants in Stockholm County, Sweden.…”
mentioning
confidence: 99%
“…throughout childhood and in young adulthood. Darlow et al have reported on the visual function13 and social outcome21 in a large cohort of preterm young adults from New Zealand, born before the introduction of treatment for ROP. Molloy et al reported on the visual function and visual perception in a cohort from Australia of individuals aged 14…”
mentioning
confidence: 99%
“…Moreover, a cross-sectional study in 10-year-old prematurely born Swedish children revealed that these children had a higher prevalence of hypermetropia of more than 3 D, or myopia of -1 D or less, astigmatism of 1 D or more, and anisometropia of 1 D or more than those born at term (20). In a recent cohort study of very LBW infants at 27-29 years in New Zealand, identified a history of untreated ROP was associated with a higher likelihood of high myopia(>5D) progression (21).…”
Section: 1risk Factors Assessmentmentioning
confidence: 99%